Assessment of Microvolt T‐Wave Alternans in High‐Risk Patients with the Congenital Long‐QT Syndrome - Schmitt, Jörn (Ann Noninvasive Electrocardiol, 2009)
Background: Microvolt T‐wave alternans (MTWA) has been used for arrhythmogenic risk stratification in cardiac disease conditions associated with increased risk of sudden cardiac death. Macroscopic T‐wave alternans has been observed in patients with congenital long‐QT syndrome (LQTS). The role of MTWA testing in patients with LQTS has not been established. Objective: To determine the diagnostic value of MTWA testing in high‐risk patients with LQTS. Methods and results: We assessed MTWA in 10 consecutive LQTS index patients who survived cardiac arrest or had documented torsade de pointes tachycardia and 6 first‐degree family members with congenital LQTS which had been genotyped in 13 of 16 subjects (7 index patients, 6 family members). No LQTS‐causing mutation was identified in 3 index patients with overt QT prolongation. MTWA was assessed during standardized bicycle exercise testing using the spectral method and yielded negative (n = 8) or indeterminate (n = 2) results in index patients, respectively. Similarly, all first‐degree family members tested MTWA negative except for one indeterminate result. Two genotype positive family members could not be tested (two children—4 and 9 years of age). Conclusion: In patients with congenital LQTS, free from structural heart disease and with a history of life‐threatening cardiac arrhythmias, assessment of MTWA does not yield diagnostic value. Hence, determination of MTWA in lower risk LQTS patients without spontaneous arrhythmic events is likely not to be useful for arrhythmia risk stratification.